Letramento e identidade: a apropriação de gêneros argumentativos na escola com a mediação do livro didático - Gomes, Glaucia Regina (2009)
Our research proposal has as its main issue the identity transformation of the student from the appropriation of certain kinds of speech in school. According to Meurer (2005), is through the genres that the subject establishes his identity, as it appropriates different discourses. The PCN (national curriculum) Portuguese Language (Brasil, 1997) points to the importance of addressing the genres that characterize the public uses of language, in which the student is projected in social practices, thus establishing its identity, toward autonomy. However, we observed through the teaching practice, students mostly do not have sufficient knowledge and experience about the social practices of literacy (Kleiman, 2007), which involve certain genres. For Bakhtin (2000), the genders are relatively stable types of utterances that are linked to typical situations of the media. In line with the concept of Bakhtin, Schneuwly (2004) considers gender as a tool, which the subject is used to appropriate the language in this social reality. However, education fails because the student does not see the sense in the production of speech based on models that are not linked to their social practice and therefore do not express their identity. We developed a qualitative and interpretive in a private school education of the city of São Carlos, with students from a class of seventh grade. Ascertain the difficulty in the production of argumentative texts, because the student is not identified in the production of these and, therefore, finds it difficult to grasp them. Based on these findings, we analyzed the data, based on some theoretical aspects of online research Fairclough (2003) which implies certain notions of ideology and power of different conceptions of identity (Hall, 2005) and new literacies Gee (2004). Thus, our work aims to contribute reflections on the teaching and learning of the language and the pedagogical exploitation of genres for the development of new teaching methodologies. Therefore, we will discuss genres as instruments whose appropriation by the subject allows for the transformation, construction and constitution of its identity.